2009
DOI: 10.1194/m900200-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids are rapidly delivered to and extracted from membranes by methyl- -cyclodextrin

Abstract: A frequently used approach for adding FA at higher concentration is to complex the FA with albumin, which allows preparation of FA that is solubilized at millimolar concentrations. Although albumin is a physiologically relevant carrier of FA, careful consideration must be given to the facts that albumin can deliver impurities to cells and can extract FA and other nutrients from cells, which could alter their metabolic state ( 3 ). In addition, there is continuing disagreement about the rates of FA dissociation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Consistent with the Hamilton Model [27][28][29], Ouellet et al [30] demonstrated that the brain transport coefficient (Clup, ll g -1 s -1 ) of [ 14 C]-DHA and [ 14 C]-eicosapentaenoic acid (EPA) was not saturable at super-physiological concentrations, up to 100 lM, suggesting that DHA and EPA cross the BBB by simple diffusion. It was also reported that, upon crossing the BBB, EPA is rapidly b-oxidized possibly explaining its low concentration within the brain [31].…”
Section: Introductionmentioning
confidence: 87%
“…Consistent with the Hamilton Model [27][28][29], Ouellet et al [30] demonstrated that the brain transport coefficient (Clup, ll g -1 s -1 ) of [ 14 C]-DHA and [ 14 C]-eicosapentaenoic acid (EPA) was not saturable at super-physiological concentrations, up to 100 lM, suggesting that DHA and EPA cross the BBB by simple diffusion. It was also reported that, upon crossing the BBB, EPA is rapidly b-oxidized possibly explaining its low concentration within the brain [31].…”
Section: Introductionmentioning
confidence: 87%
“…A proposed mechanism for fatty acid uptake is an insulin-or muscle contraction-induced translocation of fatty acid transport proteins to the plasma membrane, resulting in a net uptake of circulating fatty acids ( 26 ). However, the precise mechanism of long-chain fatty acid uptake into myocytes is still rather uncertain and is split between two prevailing hypotheses: passive diffusion-and protein-specifi c-mediated transport ( 22,(26)(27)(28)(29)(30)(31) ( Fig. 2 ).…”
Section: Fatty Acid Uptake and Intracellular Transportmentioning
confidence: 99%
“…Although albumin is frequently used, methyl-␤ -cyclodextrin (MBCD) is an alternative vehicle for the solubilization of FAs ( 25,26 ). We found that MBCD applied as described previously ( 25 ) led to an improved reconstitution of defi ned acylcarnitine standards in solution compared with albumin.…”
Section: Resultsmentioning
confidence: 76%